Modulatory effect of camel milk on intestinal microbiota of mice with non-alcoholic fatty liver disease - Hao, Shiqi; Ming, Liang; Li, Yafei; Lv, Haodi; Li, Lin; Jambal, Tuyatsetseg; Ji, Rimutu (Frontiers in Nutrition, 2022)
Non-alcoholic Fatty Liver Disease (NAFLD) is a common metabolic disease of life, usually caused by unhealthy diet and lifestyle. Compared to normal individuals, the structure of the intestinal flora of NAFLD patients is altered accordingly. This study investigates the effect of camel milk on the regulation of intestinal flora structure in mice with high-fat diet-induced NAFLD. NAFLD model was established by feeding C57BL/6J mice a high-fat diet for 12 weeks, while camel milk (3.0 g/kg/d), cow milk (3.0 g/kg/d) and silymarin (200 mg/kg/d) were administered by gavage, respectively. Food intake and changes of physiological indexes in mice were observed and recorded. The 16S rRNA gene V3-V4 region was sequenced and the intestinal flora diversity and gene function were predicted in the colon contents of mice from different group. The results showed that camel milk enhanced glucolipid metabolism by down-regulate the levels of blood glucose and triglyceride (TG) in serum, reduced lipid accumulation by down-regulate the level of TG in the liver and improved liver tissue structure in NAFLD mice (p <0.05). Meanwhile, camel milk had a positive modulatory effect on the intestinal flora of NAFLD mice, adjusting the relative abundance and diversity of the intestinal flora of NAFLD mice significantly (p<0.05), and silymarin had a similar modulatory effect. At the genus level, camel milk increased the relative abundance of Bacteroides, norank_f_Muribaculaceae and Alloprevotella and decreased the relative abundance of Dubosiella and Coriobacteriaceae_UCG-002 (p<0.05). Camel milk also enhanced Carbohydrate metabolism, Amino acid metabolism, Energy metabolism, Metabolism of cofactors and vitamins and Lipid metabolism in NAFLD mice, thus reducing the degree of hepatic lipid accumulation in NAFLD mice and maintaining the normal structure of the liver. In conclusion, camel milk can improve the structure and diversity of intestinal flora and enhance the levels of substance and energy metabolism in NAFLD mice, which has a positive effect on alleviating NAFLD and improving the structure of intestinal flora.